Phenanthridin-6-one derivatives as the first class of non-steroidal pharmacological chaperones for Niemann-Pick disease type C1 protein. Issue 12 (15th June 2017) - Fukuda, Hiromitsu; Karaki, Fumika; Dodo, Kosuke; Noguchi-Yachide, Tomomi; Ishikawa, Minoru; Hashimoto, Yuichi; Ohgane, Kenji
Graphical abstract: Abstract: Niemann-Pick disease type C is a fatal, progressive neurodegenerative disease mostly caused by mutations in Nieamnn-Pick type C1 (NPC1), a late endosomal membrane protein that is essential for intracellular cholesterol transport. The most prevalent mutation, I1061T (Ile to Thr), interferes with the protein folding process. Consequently, mutated but intrinsically functional NPC1 proteins are prematurely degraded via proteasome, leading to loss of NPC1 function. Previously, we reported sterol derivatives as pharmacological chaperones for NPC1, and showed that these derivatives can normalize folding-defective phenotypes of I1061T NPC1 mutant by directly binding to, and stabilizing, the protein. Here, we report a series of compounds containing a phenanthridin-6-one scaffold as the first class of non-steroidal pharmacological chaperones for NPC1. We also examined their structure-activity relationships.